2015
DOI: 10.1007/s13277-015-4381-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bufadienolides on HER2 overexpressing breast cancer cells

Abstract: HER2 is a proto-oncogene frequently amplified in human breast cancer, its overexpression is correlated with tamoxifen resistance and decreased recurrence-free survival. Arenobufagin and bufalin are homogeneous bufadienolides of cardiac glycosides agents. In this research, we studied the effects of arenobufagin and bufalin on cellular survival and proliferation of HER2 overexpressing breast cancer cells and the mechanism under the results including the direct effect on HER2 downstream pathways. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…For instance, our previous study showed that ARE and BFU can inhibit SRC‐1 and SRC‐3 expression in HER2‐positive breast cancer cells. Additionally, ARE and BFU can block breast cancer, glioma, and lung cancer cell proliferation 39,72‐74 . In our study, ARE and BFU suppressed the expression of SRC‐1 in GBM cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For instance, our previous study showed that ARE and BFU can inhibit SRC‐1 and SRC‐3 expression in HER2‐positive breast cancer cells. Additionally, ARE and BFU can block breast cancer, glioma, and lung cancer cell proliferation 39,72‐74 . In our study, ARE and BFU suppressed the expression of SRC‐1 in GBM cells.…”
Section: Discussionsupporting
confidence: 55%
“…Our previous study reported that arenobufagin (ARE) and bufalin (BFU; SRC inhibitor), homogeneous bufadienolides, could inhibit SRC-1 expression in HER2-overexpressing breast cancer cells. 39 Thus, in this study, ARE and BFU were used to treat LN229-EV, LN229-SRC1, and U251 cells at 50 nmol/L for 48 hours. The results showed that the expression of SRC-1, XIST, and KLF4 had all obviously declined in control and SRC-1 overexpression cells (Figure 8A-C).…”
Section: Arenobufagin and Bufalin Inhibit Proliferation And Stemness ...mentioning
confidence: 99%
“…As an inhibitor of SRC-3, bufalin reduced tumor growth in an MDA-MB-231-LM3.3 xenograft tumor model. Yuan et al [42] have found that ABF inhibits the proliferation and survival of HER2-overexpressing breast cancer MCF-7/HER2 and T47D/HER2 cells through the inhibition of AKT, ERK and E2F1. Instead of these reported mechanisms, we find that ABF-induced phosphorylation of YAP through JNK signaling enhances the p73-mediated transcription of Bax and p53AIP1 , and subsequently induces apoptosis in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that ABG and BF could significantly inhibit the proliferation and survival of HER2 overexpressing breast cancer cells, and downregulate the expression of SRC-1, SRC-3, nuclear transcription factor E2F1, phosphorylated AKT and ERK. The combination of low-dose bufadienolides and tamoxifen could significantly enhance the inhibitory effect of tamoxifen on HER2 overexpression breast cancer cells, which suggested that ABG and BF might be potential adjuvant therapy drugs for the treatment of HER2 overexpression breast cancer [ 30 ]. Paclitaxel (PTX) is an effective drug for the treatment of cancer [ 31 ].…”
Section: Pharmacological Activities Of Bufadienolidesmentioning
confidence: 99%